The Intersectionality of Race and Gender in Financial Planner Use - Miranda Reiter; Di Qing; NaRita Anderson; Kimberly Watkins (Journal of Financial Therapy, 2022)
Using the 2019 Survey of Consumer Finances, this study examined the role of race and gender regarding the use of financial planners through the lens of intersectionality. More specifically, this study investigated whether there was an association between race and gender, notably for Black women, and financial planner use compared to White women, Black men, and White men. Results of the interaction analyses in the probit model show that Black women were more likely to use financial planners than other groups. A follow-up analysis indicated that results were significant when comparing Black women to White men but there was no significant difference when comparing Black women to Black men and White women. This study adds to the literature by taking into consideration the implications of dual minority status on Black women’s financial well-being and decision-making. Implications are provided for financial therapists and professionals, policymakers, and funders.
Keywords: financial help-seeking; financial planner use; race; gender; intersectionality